ANOMALI POLA ASUH: KERATON YOGYAKARTA, 1921-1939 (Paramita: Historical Studies Journal, 2016)
This paper is a historical study of the shifting of parenting pattern in Keraton Yogyakarta during Sri Sultan Hamengkubuwono VIII. In the custom of the family life in Keraton Yogyakarta, especially for the royal family, a newborn child was cared by parents and housekeepers (mbok mban/abdi dalem). However, the changes was happened in the period of Sri Sultan Hamengkubuwono VIII. The Dependency of chain parenting against house aids was changed through storage sons of kings in the European family. In this condition, the anomaly was happened because in the midst of the parenting, Sultan is responsible to maintaining and reproducing the Javanese culture in the palace. Because of that, Sultan would entrust to the European family upbringing. This condition is certainly vulnerable to the overall sustainability of Javanese culture. Tulisan ini merupakan kajian historis terhadap pergeseran pola asuh yang terjadi di Keraton Yogyakarta pada masa Sri Sultan Hamengku Buwono VIII. Suatu kebiasaan dalam kehidupan keluarga Jawa, terutama dalam keluarga keraton bahwa seorang anak yang baru lahir selain diasuh oleh orang tua juga diasuh oleh pembantu rumah tangga (mbok mban/abdi dalem). Akan tetapi, perubahan pola asuh terjadi pada masa Sri Sultan Hamengkubuwono VIII. Rantai ketergantungan pola asuh terhadap pembantu rumah tangga diubah melalui penitipan putra-putra raja pada keluarga Eropa. Dalam kondisi inilah anomali pola asuh kemudian terjadi. Ini terjadi karena di tengah-tengah tanggung jawab Sultan untuk tetap mempertahankan dan mereproduksi budaya Jawa di dalam lingkungan keraton, ia justru mempercayakan pola asuh pada keluarga Eropa, yang pada akhirnya memberikan pengaruh yang tidak sedikit pada keberlangsungan kebudayaan Jawa.